Improving English Speaking Performance Through Discussion Games - Jumli Alam Mapgun; Muhammad Aulia (English Education Journal, 2022)
This experimental research aims to justify whether Discussion Games improve students’ performance in speaking and to examine the students’ performance in learning speaking through the application. A total of 60 students involved in the study and they were divided equally for both the experimental and control groups. The data were collected from the pre-test, the treatment, the post-test, and questionnaire. The speaking test was given to both groups and the test scores were assessed by two examiners. The data were analyzed and interpreted using the SPSS 17.0 software program. The results reveal that the text types of Discussion Gamescan improve students’ performance in speaking and the application of Discussion Games increase students’ performance in learning speaking. The result of the students’ speaking score from the pre-test to the post test demonstrates a significant difference with Sig. (2 tailed) is lower than 0.05. Furthermore, the comparison of the students’ speaking improvement between the experimental and control groups is 0.000. It means that the improvement is recognized to be of significance and Discussion Games can increase students’ performance in speaking. The findings suggest that the experimental class responded positively to Discussion Games and confirmed that the strategy help them improve their speaking skills.